1998
DOI: 10.1046/j.1365-2168.1998.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging results of split-liver transplantation

Abstract: These encouraging results compare favourably with those of reduced-size and whole-liver transplantation and justify wider application of this technique, thereby optimizing donor resource use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…One left-lateral segment graft only was lost because of recurrent biliary complications, leading to biliary cirrhosis and requiring retransplantation. Although excellent outcomes have been reported using the ex situ split-liver technique (18,29), in our experience, the in situ technique has played a key role in diffusing split liver through easier and safer liver graft sharing between centers. This article does not directly address the outcome of the right split grafts; however, our group and others have reported patient and graft-survival rates of right split-graft recipients to be comparable with those obtained with whole grafts from cadaveric donors (17,23).…”
Section: Complicationsmentioning
confidence: 88%
“…One left-lateral segment graft only was lost because of recurrent biliary complications, leading to biliary cirrhosis and requiring retransplantation. Although excellent outcomes have been reported using the ex situ split-liver technique (18,29), in our experience, the in situ technique has played a key role in diffusing split liver through easier and safer liver graft sharing between centers. This article does not directly address the outcome of the right split grafts; however, our group and others have reported patient and graft-survival rates of right split-graft recipients to be comparable with those obtained with whole grafts from cadaveric donors (17,23).…”
Section: Complicationsmentioning
confidence: 88%
“…Although concerns about outcomes for split liver grafts were raised (9,10), favorable reports from single centers have been published (11)(12)(13)(14)(15)(16). Most studies demonstrated good results for pediatric recipients of the left-sided split grafts, but partial or split liver grafts transplanted into adults had a higher rate of failure, leading to increased need for re-transplantation and potentially higher death rate for recipients (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that, from a surgical point of view, the whole graft seems to be the safest graft, split liver transplantations in children have yielded comparable results [3,[11][12][13][14][15][16]. Transplantation of a left lateral graft resulting from splitting of a cadaveric donor liver can also achieve comparable results with that of transplanting left lateral grafts from living donors [16,17].…”
Section: Resultsmentioning
confidence: 85%